2019
DOI: 10.1016/j.ebiom.2019.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of ALK mutations mediating ALK-TKIs resistance and drug re-purposing to overcome the resistance

Abstract: Background Alectinib has shown a greater efficacy to ALK -rearranged non-small-cell lung cancers in first-line setting; however, most patients relapse due to acquired resistance, such as secondary mutations in ALK including I1171N and G1202R. Although ceritinib or lorlatinib was shown to be effective to these resistant mutants, further resistance often emerges due to ALK-compound mutations in relapse patients following the use of ceritinib or lorlatinib. However, the dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
119
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 109 publications
(127 citation statements)
references
References 42 publications
8
119
0
Order By: Relevance
“…MET gene amplification, which is well‐known as EGFR‐TKI resistance, a cause of bypass pathway activation‐mediated resistance to alectinib or ceritinib, was identified in 1 specimen. L1196M + G1202R, a compound mutation, was also a resistance mechanism to lorlatinib in patients with L1196M who previously experienced relapse while on crizotinib treatment …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…MET gene amplification, which is well‐known as EGFR‐TKI resistance, a cause of bypass pathway activation‐mediated resistance to alectinib or ceritinib, was identified in 1 specimen. L1196M + G1202R, a compound mutation, was also a resistance mechanism to lorlatinib in patients with L1196M who previously experienced relapse while on crizotinib treatment …”
Section: Resultsmentioning
confidence: 99%
“…Second, secondary mutation may be observed more frequently in patients with crizotinib resistance in our cohort compared to previous reports, which may be due to the relatively higher plasma concentrations of crizotinib among Japanese ALK (+) patients than among Caucasian patients, as indicated by Fujiwara et al Third, additional mutation in the ALK kinase domain, which mediates acquired resistance to ALK‐TKI, usually emerges during crizotinib, ceritinib and alectinib failure, whereas a compound mutation in the kinase domain was the only resistance mechanism identified in lorlatinib failure. The compound mutation leading to lorlatinib failure has been reported by Shaw AT et al, Yoda et al and Okada et al in a preclinical model and in some clinical cases . Although Okada and his colleagues have shown that the use of early‐generation ALK‐TKI and several BCR‐ABL inhibitors might treat double mutation after lorlatinib failure, a strategy that can treat this type of resistance has not yet been established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the search for drugs that can overcome these compound mutations is crucial and urgent. Several reports have shown that some of the lorlatinib‐resistant compound mutations became resensitized to first‐ or second‐generation ALK inhibitors (e.g., C1156Y + L1198F became resensitized to crizotinib, and I1171N + L1256F became resensitized to alectinib) …”
Section: Introductionmentioning
confidence: 99%
“…However, in several reports, diverse compound ALK mutations were identified in lorlatinib-resistant cells or patient samples after these patients had received the sequential ALK-TKI treatments. [7][8][9] The previously reported compound mutations found in patients are F1174V + G1202R, 10 C1156Y + L1198F, 7 E1210K + S1206C, E1210K + D1203N, 4 C1156Y + L1198F, I1171N + L1198F, L1171N + D1203N, L1196M + G1202R, G1202R + G1269A, D1203N + E1210K, G1202R + L1204V + G1269A, D1203N + E1210K + G1269A, 8 R1192P + G1202R, 11 G1202R + G1269A, 12 F1174L + G1202R, T1151M + G1202R, 13 L1196M + G1202R, I1171N + D1203N. 14 Therefore, the search for drugs that can overcome these compound mutations is crucial and urgent.…”
Section: Introductionmentioning
confidence: 99%